Mitral and aortic regurgitation following transcatheter aortic valve replacement - Szymański, Piotr (Heart, 2016)
OBJECTIVE: To analyse the impact of postprocedural mitral regurgitation (MR), in an interaction with aortic regurgitation (AR), on mortality following transcatheter aortic valve implantation (TAVI). METHODS: To assess the interaction between MR and AR, we compared the survival rate of patients (i) without both significant MR and AR versus (ii) those with either significant MR or significant AR versus (iii) with significant MR and AR, all postprocedure. 381 participants of the Polish Transcatheter Aortic Valve Implantation Registry (166 males (43.6%) and 215 females (56.4%), age 78.8±7.4 years) were analysed. Follow-up was 94.1±96.5 days. RESULTS: Inhospital and midterm mortality were 6.6% and 10.2%, respectively. Significant MR and AR were present in 16% and 8.1% patients, including 3.1% patients with both significant MR and AR. Patients with significant versus insignificant AR differed with respect to mortality (log rank p=0.009). This difference was not apparent in a subgroup of patients without significant MR (log rank p=0.80). In a subgroup of patients without significant AR, there were no significant differences in mortality between individuals with versus without significant MR (log rank p=0.44). Significant MR and AR had a significant impact on mortality only when associated with each other (log rank p<0.0001). At multivariate Cox regression modelling concomitant significant MR and AR were independently associated with mortality (OR 3.2, 95% CI 1.54 to 5.71, p=0.002). CONCLUSIONS: Significant MR or AR postprocedure, when isolated, had no impact on survival. Combined MR and AR had a significant impact on a patient's prognosis.